2005
DOI: 10.2174/157016105774329453
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 and Human Platelets

Abstract: There is conflicting evidence regarding the effect of endothelin-1 (ET-1) on platelets. Some studies show that ET-1 activates platelets, others show platelet inhibition with ET-1 and some studies did not detect an effect of ET-1. These conflicting results may be due to complex interactions between platelet ET(A) and ET(B) receptors. ET-1 antagonism may emerge as an important therapeutic strategy in the management of several vascular disorders. However, to date the only prescribed ET-1 antagonist is bosentan fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 95 publications
0
15
0
2
Order By: Relevance
“…We detected a modest enrichment of genes involved in ''cell-to-cell signaling and interaction'' (range, P = 4.52 3 10 À2 to 1.17 3 10 À1 , Benjamini-Hochberg corrected for multiple testing; n = 10). Notably, these genes included THBS1 (encoding thrombospondin 1), WASL (Wiskott-Aldrich syndrome-like), and EDN1 (endothelin 1), which have a marked role in the activation of blood platelets (Dorahy et al 1997;Falet et al 2002;Jagroop et al 2005). This suggests the involvement of non-cell-autonomous mechanisms for the regulation of platelet count, whereby extrinsic factors expressed by MOs or their progeny regulate the differentiation and proliferation of the hematopoietic stem cells toward MKs and the removal of senescent platelets from the circulation by liverresiding MO-derived macrophages.…”
Section: Enrichment Patterns Of Snps Associated With Closely Related mentioning
confidence: 99%
“…We detected a modest enrichment of genes involved in ''cell-to-cell signaling and interaction'' (range, P = 4.52 3 10 À2 to 1.17 3 10 À1 , Benjamini-Hochberg corrected for multiple testing; n = 10). Notably, these genes included THBS1 (encoding thrombospondin 1), WASL (Wiskott-Aldrich syndrome-like), and EDN1 (endothelin 1), which have a marked role in the activation of blood platelets (Dorahy et al 1997;Falet et al 2002;Jagroop et al 2005). This suggests the involvement of non-cell-autonomous mechanisms for the regulation of platelet count, whereby extrinsic factors expressed by MOs or their progeny regulate the differentiation and proliferation of the hematopoietic stem cells toward MKs and the removal of senescent platelets from the circulation by liverresiding MO-derived macrophages.…”
Section: Enrichment Patterns Of Snps Associated With Closely Related mentioning
confidence: 99%
“…However, as recently reviewed, ET-1 effects on platelets are still conflicting [328]: some studies showed that in vitro exposure to ET-1 induces platelet activation or increases platelet responses to aggregating agonists [327329], other studies, however, failed to detect any direct effect [329] or even showed a decrease in platelet responses [328]. …”
Section: Influence Of Adipocytokines On Platelets and Vascular Smomentioning
confidence: 99%
“…52 However, the effect of ET-1 on platelets is still controversial. 53 Resveratrol, a natural polyphenolic compound extracted from plants, seems to inhibit platelet aggregation and change platelet reactivity in inflammatory processes including acute pancreatitis. 54,55 There is also some evidence that resveratrol prevents leukocyte recruitment and endothelial barrier disruption in ischemic/reperfusion injury 56 and that it upregulates nitric oxide synthase mRNA expression in endothelial cells.…”
Section: Pathophysiology Of Hemostatic Disorders In Acute Pancreatitimentioning
confidence: 99%